The dynamization of pesantren in islamic education: a visionary perspective of abdurrahman wahid - Suyuti, Imam; Prihantoro , Wahyu Kholis; Sumiati , Endang (At-Tajdid: Jurnal Ilmu Tarbiyah, 2025)
This article presents a comprehensive exploration of the concept of pesantren dynamization in Islamic education from the visionary perspective of Abdurrahman Wahid, affectionately known as Gus Dur. It delves deeply into Wahid’s profound insights and visionary ideas regarding how pesantren, the traditional Islamic boarding schools, can adapt and thrive in the ever-evolving landscape of contemporary society. Wahid’s philosophy revolves around the notion that pesantren should not merely serve as centers of religious instruction but should transform into dynamic engines of positive societal change. Wahid underscores the imperative for pesantren to undergo a paradigm shift in their curriculum, teaching methodologies, and their societal engagement. . Ultimately, this article showcases how Abdurrahman Wahid’s forward-thinking perspective envisions pesantren as dynamic hubs of education and social betterment. His philosophy encourages these institutions to retain their cherished traditions while embracing contemporary values, with the ultimate goal of transforming them into ideal educational centers that not only enrich their students’ lives but also contribute to the broader advancement of society.